Effectiveness of internet-delivered cognitive behavioural therapy for anxiety and obsessive-compulsive disorders within routine clinical care in rural Sweden - Sarah Vigerland; Sandra Fredlander; Kristina Aspvall; Maral Jolstedt; Fabian Lenhard; David Mataix-Cols; Brjánn Ljótsson; Eva Serlachius (Internet Interventions, 2024)
Few studies have evaluated the implementation of ICBT in regular child and adolescent mental health services (CAMHS). This study aimed to explore the acceptability, feasibility, and effectiveness of ICBT for children and adolescents with anxiety disorders and obsessive-compulsive disorder (OCD) within a rural CAMHS. The study also explored outcome predictors and long-term outcomes.Eighty-three participants were consecutively recruited from a non-specialized CAMHS in Region Jämtland Härjedalen in northern Sweden. Therapist-guided ICBT was offered during 12 weeks to children aged 8–17 with an anxiety disorder or OCD. Acceptability and feasibility measures included treatment adherence, treatment satisfaction, and adverse events. The primary outcome measure was the Clinical Global Impression–Severity. Secondary measures of effectiveness included clinician-, self-, and parent-ratings of symptom severity and functional impairment. Assessments were completed at baseline, post-treatment, and three-month follow-up (primary endpoint). A two-year follow up was conducted using medical records. Potential predictors included both patient characteristics and treatment variables.Results indicated that ICBT was both acceptable and feasible according to study measures. Statistically significant improvements were found from baseline to the three-month follow-up on clinician rated severity (B [SE] = −0.92 [0.09]; p < .001), as well as on all secondary measures. Forty-three percent of participants no longer fulfilled criteria for their principal disorder at the three-month follow-up. No serious adverse events were reported. Clinical improvement was highest among children with higher functioning at baseline (B [SE] = −0.05 [0.02]; p < .05). Forty-six percent of participants had been in contact with CAMHS during the two-year follow-up period, mainly for reasons other than their initial diagnosis. Findings suggest that ICBT could be an acceptable and feasible treatment option for young people with anxiety disorders and OCD in ...